2011
DOI: 10.1186/1752-1947-5-295
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary intravascular lymphoma diagnosed by 18-fluorodeoxyglucose positron emission tomography-guided transbronchial lung biopsy in a man with long-term survival: a case report

Abstract: Introduction18-Fluorodeoxyglucose positron emission tomography can detect the pulmonary involvement of intravascular lymphoma that presents no abnormality in a computed tomography scan.Case presentationWe report the case of a 61-year-old Japanese man who had pulmonary intravascular lymphoma and no computed tomography abnormality. We were able to make an antemortem diagnosis of pulmonary intravascular lymphoma by transbronchial lung biopsy according to 18-fluorodeoxyglucose positron emission tomography findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In this setting, several authors have reported that FDG‐PET could be useful for the diagnosis of IVLBCL when this type of lymphoma is clinically suspected . The potential interests of FDG‐PET/CT in IVLBCL reported in literature are summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, several authors have reported that FDG‐PET could be useful for the diagnosis of IVLBCL when this type of lymphoma is clinically suspected . The potential interests of FDG‐PET/CT in IVLBCL reported in literature are summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
“…When diagnosed early, it is, however, potentially treatable [2,11]. In this setting, several authors have reported that FDG-PET could be useful for the diagnosis of IVLBCL when this type of lymphoma is clinically suspected [3,4,[7][8][9][10][12][13][14][15][16][17][18][19][20][21][22]. The potential interests of FDG-PET/CT in IVLBCL reported in literature are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier reports, IVLBCL was diagnosed by biopsy of involved organs including the lung, lacrimal gland and prostate [9,10,11]. In 81 IVLBCL cases reported by Murase et al [12] the diagnostic sites were the bone marrow (54), liver (14), spleen (6), lung (5) and the adrenal gland, brain and kidney (2).…”
Section: Discussionmentioning
confidence: 99%
“…FDG PET has been considered a “metabolic biopsy” [39] tool in the evaluation of nonlung lesions with indeterminate biopsy results. Niida et al [40] reported a case in which pulmonary intravascular lymphoma was diagnosed with FDG PET–guided transbronchial lung biopsy. Purandare et al [28] found that lung biopsies were performed only after the needle tip was confirmed to be in the portion of the lesion corresponding to the hypermetabolic area seen on PET images.…”
Section: Chestmentioning
confidence: 99%